The relationship between gender perception levels and infertility distress of infertile women in a university hospital, Turkey - Dogan Yuksekol, Ozlem; Duman, Mesude; Durgun Ozan, Yeter (Emerald Group Publishing Ltd, 2022)
Purpose This study was conducted to analyze the correlation between gender perception and infertility distress of infertile women. Design/methodology/approach This was a descriptive-analytical study conducted with 255 women receiving treatment in the in vitro fertilization unit of a medical faculty hospital in Turkey. Study data were collected using sociodemographic questions as well as the Perception of Gender Scale (PGS) and the Infertility Distress Scale (IDS). Findings It was found that the PGS mean score was 69.65 and the IDS mean score was 53.1. It was determined that there was a negative, moderate and significant correlation between gender perception and infertility distress levels of women in the infertility treatment process (r = -0.263, p < 0.001). Originality/value As a result of the study, a negative, moderate, significant correlation was detected between gender perception and infertility distress.
Keywords: Infertility; Turkish women; Gender; Infertility distress